Long-term analysis of land cover changes resulting from mining activities: Strzelin case study (S–W Poland) - K. Romańczukiewicz; J. Górniak-Zimroz (Scientific Reports)
Abstract This study describes the results of research work on the long-term analysis of land cover changes caused by mining activities in the Strzelin quarries between 1884 and 2023. The primary aim of this study was to analyse long-term landscape changes resulting from granite and gneiss extraction, using a land cover classification adapted to mining conditions. To achieve this, a methodological framework was developed that combines historical cartographic sources with geospatial data, enabling a reconstruction of post-mining land transformations. The framework incorporated rarely utilized historical maps such as 19th-century Messtischblatt maps, with spatial datasets including orthophotos and geospatial databases. The methodology is based on georeferencing and manual vectorisation of open-access data, followed by classification and topological validation to ensure spatial consistency across the time series. The results of the study indicate significant changes in the landscape, in particular an almost threefold increase in the area of mining sites between 2004 and 2023, as well as the appearance of spontaneous vegetation succession and formation of water bodies in areas where mines have been liquidated. The study also documents parallel urbanisation trends and infrastructure development, highlighting the complex interaction between industrial activity and socio-environmental processes. This work contributes to research on land use and land cover (LULC) by extending the time frame of the analysis beyond the limitations of satellite era data and filling a gap in the literature on land use changes caused by mining activities. The proposed approach is transferable to small and medium-sized areas and supports evidence-based spatial planning, land reclamation, and heritage preservation in post-industrial environments on the basis of actions taken in Strzelin and Mikoszów.